A text criticism of Hikayat Si Miskin: A textological study of writing and use of letters - Nurizzati Nurizzati; Hasanuddin WS; Novia Juita; Muhammad Ismail Nasution; Hanifah Yulia Sari; Zulfadhli Zulfadhli (BAHASTRA, 2023)
This research aim to describe a textological study of the issue of how the Hikayat Si Miskin manuscript text from the Harvad University - Houghton Library/ ms_Indo_18-METS collection was translated into handwritten Arabic-Malay script, the appearance of which is much different from the standard form of the letters of this script. This is the most important part in the textological study of the subfield of philology before the editing of texts from the old Malay Arabic-Malay script into Latin script is presented. His identity as the author is not included at the front of his work, but at the end of the manuscript called the colophon. The presentation of a text that has been cleaned of all writing errors paves the way for further study of the content of the text from various aspects related to the existence of the form and content of the text being studied, such as a study of the structural content of the text, a study of linguistic aspects, a study of social values. and culture, it is even possible to examine historical elements, because manuscripts are historical documents that describe the life systems and patterns of old society. The method used to discuss text issues and content that can be studied in various related scientific disciplines is the standard text criticism method, namely a philological method that attempts to re-present classical texts by criticizing and correcting corrupt texts. In accordance with the focus of the discussion which focuses on writing and visual text writing, the research results found writing irregularities and errors in writing lacunae, substitutions, additions, transpositions, dittography, and haplography. The most common writing errors are substitution errors.